Strategies for Increasing Internationalization In Furniture Smes In Lamongan Regency - Mohammad Yaskun; Sudarmiatin; Rosmiza Bidin (Jurnal Mantik, 2022)
This study discusses the opportunities, challenges, strengths and weaknesses of furniture SMEs in Lamongan Regency. The results of the Assessment will be used as a basis for developing an internationalization improvement strategy. The analysis used in this research is SWOT analysis and external internal matrix. The results showed that furniture SMEs in Lamongan Regency had strengths and good opportunities in improving their international performance. Based on the existing environment, these SMEs are in a determined position (carefully). Therefore, a suitable business strategy to be developed is a product development strategy by focusing on developing product diversification, differentiating, branding of products, maximizing cooperation in shipping goods, and increasing the number of alternative suppliers, in order to improve international quality.